(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The author investigated the features of mobile advertising. Rich Communication Services is a progressive text-messaging tool that combines different communication standards, integrated into an application, will allow users to create group conversations, share media files, and in the long run make video calls, with supporting the standards of the SMS and MMS. The new tools for advertising are emerging with the development of mobile internet and the widespread use of smartphones. It was highlighted the advantages and disadvantages of mobile advertising. The benefits of mobile advertising are low cost, proximity to the consumer, targeting, and information storage. Disadvantages are an inconvenience for the 40+ target audience, limitations of mobile networks, and the ability of customers to use mobile phones. The new generation creates a new large-scale market. It can quickly adapt to innovation and is very attractive to many manufacturers and sellers. The analysis has shown that consumers typically deleted mobile messages, except for those that gave them some benefit, such as a discount coupon or the need to appear at a specific time and place where they would benefit. It is important to adjust the content of the message, as well as the place and time of its receipt according to the individual expectations of the addressees. Therefore, it is necessary to collect the information about the recipient, which is not always easy, because consumers are reluctant to provide their data to producers and sellers. The success of enterprises in the mobile advertising market depends on the knowledge of the features and the behavior of its clients. It was proved that the effectiveness of mobile advertising is determined by the needs of its consumers. The marketing automation systems should be used to identify those needs.